Analisis Kolaborasi Pemerintah dan UMKM dalam Mendorong Ekspor Kota Bandung di Tengah Tantangan Global - Minhajuddin Minhajuddin; Nurul Aziz Pratiwi; Dhenahi Jerfiani Wendiyana (Indonesian Journal Publisher, 2026)
During the period of January until December 2024, West Java was the province with the highest export value, reaching USD 37,872.3 million. Nevertheless, West Java still possesses a significant export potential that must be elaborated on by all stakeholders. This study aims to elaborate on the government’s strategies to increase the export volume of SMEs in Bandung City. The study employs a qualitative approach with a descriptive research design. The qualitative approach was chosen because this research seeks to gain an in-depth understanding of the government’s strategies in promoting the growth of SME exports in Bandung City amid global challenges. Data analysis techniques was conducted using Nvivo software. The results indicate that there are six critical aspects that the government must consider to enhance exports: training and regulations, institutional support and mentoring, technical and logistical facilities, promotional media, trade diplomacy, market access, as well as collaboration and networking.